Efficacy of long-acting somatostatin analogs in recurrent variceal bleeding in a patient with pre-hepatic portal vein thrombosis - Alempijević, Tamara; Balović, Ana; Pavlović Marković, Aleksandra; Tarabar, Dino; Krstić, Miodrag; Miljić, Predrag; Bjelović, Miloš (Vojnosanitetski pregled, 2015)
Introduction. Bleeding from esophageal varices is a serious medical problem because of the risk of recurrent bleeding and high mortality rate (17–54%). Gastroesophageal varices develop in 50% of cirrhotic patients with portal hypertension, but can also develop in other pre- or post-hepatic causes of portal hypertension. Case report. We reported a 48-year-old female patient with portal hypertension caused by mesenterial vein thrombosis due to congenital thrombophilia. The patient was hospitalized several times because of recurrent gastroesophageal bleeding. Thrombosis of portal, lienal and mesenteric veins was diagnosed using multislice computed tomography (MSCT) angiography. Sclerotherapy and/or variceal ligation could not be used due to variceal size and distribution. Beta blockers were ineffective. Balloon tamponade and octreotide were used in each massive bleeding episode. Carvedilol therapy was introduced but rebleeding occured. Surgical treatment was considered a high risk procedure due to massive thrombosis of mesenterial veins, patient`s general condition and high risk of postoperative thrombotic events. Thus, long-acting somatostatin analogue – Sandostatin® LAR was initiated at a dose of 30 mg im/month. The patient responded to the therapy well and variceal bleeding did not occur for the following 3 months. After 3 months another episode of gastric variceal hemorrhage occurred and surgical treatment was reconsidered. Total gastrectomy was performed in order to prevent repeated bleeding from large gastric varices and the patient recovered successfully, and after 1 year is symptom-free. Conclusion. Long-lasting somatostatin analogue was used for the first time in treatment of gastroesophageal variceal hemorrhage in the patient with prehepatic portal hypertension. It was effective as temporary therapeutic option allowing the improvement of the patients general condition and adequate planning of elective surgical procedure. Futher reports are needed in order to compare efficacy in treatment of patients with variceal bleeding, where poor outcome is expected.